Dinamika psikologis fangirl k-pop - Risa Almaida; Sandy Agum Gumelar; Adinda Azmi Laksmiwati (Fakultas Psikologi, 2021)
The aim of this research is to exploring the psychology dynamics of K-Pop fangirl. Data were analyzed through descriptive qualitative method which obtained through interview. Subject selected based on purposive sampling method. The result showed that: a) Fangirls idolize K-Pop because of Idol music and Idol visual aspects. b) The three subjects are in Intense personal feeling level of Celebrity worshipping behavior. Each of them also feels like have an emotional attachment towards their idol. c) One of the subjects seems like have a sense of owning them (Bias is mine behavior). Subject thinks that every idol who has a romantic relationship towards another girl same as they betray their fans. d) There is also fujoshi behavior (in Japanese) in one of the subjects, a term of women who does like romantic interaction between same-sex (Bromance).